The Evolution of Social Disorganization Theory: Historical Foundations, Contemporary Developments, and Future Directions - Karaaslan, Fadime Gokce (International Journal of Criminology and Sociology, 2026)
Social disorganization theory remains one of the most influential frameworks for understanding the relationship between neighborhood characteristics and crime. This paper reviews the historical development and theoretical evolution of social disorganization theory, from its origins in the Chicago School to its contemporary applications in criminological research. Particular attention is given to the contributions of Robert E. Park and Ernest W. Burgess, Clifford R. Shaw and Henry D. McKay, Ruth R. Kornhauser, Robert J. Bursik Jr., and Harold G. Grasmick, and Robert J. Sampson. The paper examines how the theory has expanded beyond its original focus on poverty, residential instability, and ethnic heterogeneity to incorporate concepts such as social capital, collective efficacy, social networks, and spatial processes. In addition, recent empirical developments and theoretical refinements are discussed to assess the theory’s continuing relevance in explaining crime and deviance. The paper concludes by highlighting future directions for research and the importance of integrating contemporary methodological approaches with traditional ecological perspectives. By synthesizing classical and contemporary perspectives, this review highlights the enduring relevance and adaptability of social disorganization theory in modern criminological research. In addition, the paper proposes an integrative framework that links structural conditions, social networks, social capital, collective efficacy, and spatial processes within a unified perspective on social disorganization.